RELATIONSHIP OF FAMILY ROLE WITH KNOWLEDGE OF YOUTH REPRODUCTIVE HEALTH IN DARMAIS HEALTH VOCATIONAL SCHOOL OF NURSING DEPARTMENT OF PADANGSIDIMPUAN 2018 - nelly karlinah (STIKes Mitra Husada Medan, 2019)
ABSTRACT Adolescence is a period of rapid growth and development both physically, psychologically and intellectually (Indonesian Ministry of Health, 2015). In the world, as many as 11% of pregnancies occur every year among adolescents (UNICEF, 2012). In Latin America and the Caribbean as many as 35-52% of adolescents experience unplanned pregnancies due to a lack of knowledge about pregnancy and menstruation (Aine & Maddaleno, 2003). Adolescent's knowledge about reproductive health is still low, this is evidenced by research conducted in Brazil that knowledge of puberty in 399 adolescents, as many as 57.6% were of low knowledge (Gomes, 2002). The purpose of the study was to determine the relationship of the role of families with knowledge of adolescent reproductive health in the Nursing Health Department of Darmais Padangsidimpuan Department. Type of analytic research with cross sectional approach, The sample in this study used the technique of